Park Geun-hye: als Präsidententochter zur ersten Staatspräsidentin Südkoreas? - Momoyo Hüstebeck (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2006)
Die ehemalige konservative Oppositionsführerin Park Geun-hye (2004-2006) gilt als aussichtsreiche Kandidatin für die kommenden Präsidentschaftswahlen im Dezember 2007. Die Tochter des so genannten Entwicklungsdiktators Park Chung-hee, der während seines Regimes (1961-1979) den wirtschaftlichen Aufschwung des Landes in die Wege leitete, konnte oder wollte bis dato nicht aus dem Schatten ihres Vaters heraustreten. Sie nutzte die Nostalgie für ihren Vater während der regionalen Wirtschaftskrise Ende der 1990er als Einstieg für ihre politische Laufbahn. Ihre familiäre Herkunft ist über ihr daraus resultierendes politisches Netzwerk, ihre konservative Wahlhochburg und ihre traditionell weibliche Erscheinung hinaus ihr stärkstes politisches Kapital. – – The former conservative opposition leader Park Geun-hye is seen as one of the leading contenders for the presidency in South Korea in December 2007. The daughter of Park Chung-hee (who ruled with an iron fist from 1961, after a military putsch, until 1979, when he was assassinated), has doggedly set about reviving her father's political reputation. She profited from nostalgia for her father's developmental successes when the country faced economic crisis at the end of the 1990s and the failure of a number of his democratic successors. Park Geun-hye who was the opposition leader of the conservative Grand National Party (GNP) from 2004 to June 2006 has not yet developed her own political agenda. Because of party structures based on personal networks her dynastic heritage and her cultivation of traditional female virtues and values are her strongest political assets.
Keywords: 330; Park Geun-hye; Park Chung-hee; politische Dynastien; ideologische und regionale cleavages; politische Rekrutierung; politische Repräsentation von Frauen; political dynasties; ideological and regional cleavages; political recruitment; political representation of women; Politiker; Südkorea